1998
DOI: 10.1161/01.str.29.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Impending Hemorrhagic Transformation in Ischemic Stroke Using Magnetic Resonance Imaging in Rats

Abstract: Background and Purpose-Hemorrhagic transformation (HT) of ischemic brain tissue may occur in stroke patients either spontaneously or after thrombolysis. A method to assess the risk of HT in ischemic tissue after stroke would improve the safety of thrombolytic therapy. As a means of predicting HT, we investigated the role of contrast-enhanced MRI at acute time points in a rat middle cerebral artery occlusion model with reperfusion. Methods-Intraluminal suture occlusion of the middle cerebral artery was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 44 publications
1
68
1
Order By: Relevance
“…Abnormal BBB permeability can be seen qualitatively as parenchymal enhancement in conventional delayed postgadolinium enhanced MR imaging, with enhancement in the early period of AIS being predictive of HT. [32][33][34] A conventional contrast-enhanced CT is not a component of our multimodal stroke series protocol, and no contrast-enhanced CT or MR imaging was performed during the follow-up period for our cohort. Therefore, we could not assess for conventional parenchymal enhancement in a region with elevated PS.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal BBB permeability can be seen qualitatively as parenchymal enhancement in conventional delayed postgadolinium enhanced MR imaging, with enhancement in the early period of AIS being predictive of HT. [32][33][34] A conventional contrast-enhanced CT is not a component of our multimodal stroke series protocol, and no contrast-enhanced CT or MR imaging was performed during the follow-up period for our cohort. Therefore, we could not assess for conventional parenchymal enhancement in a region with elevated PS.…”
Section: Discussionmentioning
confidence: 99%
“…Reperfusion was performed approximately 3 h following MCA occlusion by withdrawing the filament until its tip was visible in the ECA and it no longer occluded the MCA or restricted flow in the ICA. This model usually produces petechial hemorrhages in the preoptic area (POA) and caudate-putamen (CPU) at 24 h after MCA occlusion (11)(12)(13).…”
Section: Animal Preparationmentioning
confidence: 99%
“…Techniques capable of characterizing BBB integrity may prove particularly valuable in this regard, because there is a credible association between BBB disruption and HT. 3,4 Studies performed both in rats [5][6][7] and in patients with AIS 8,9 have indicated that permeability imaging with T1-weighted DCE-MR imaging may offer a viable strategy for detecting BBB disruption in the early hours following stroke onset, with significant increases in permeability estimates corresponding to areas of subsequent HT.…”
mentioning
confidence: 99%